Current minimally invasive and endourological therapy in pediatric nephrolithiasis - N. Khater; R. Abou Ghaida; R. Khauli; Y. El Hout (African Journal of Urology, 2014)
Introduction: Children with complex urinary tract stones present a treatment challenge. There is still no clear consensus regarding their management. Therefore, our goal was to review the endourological therapies in children presenting with complex nephrolithiasis, updated to 2013. Methods: This was a review of published articles, from 1981 to 2013, related to pediatric nephrolithiasis, staghorn calculi, lower pole kidney stones, and uninephric children. The sites from which information was retrieved covered PubMed, the American Urological Association, and Medline. Results: We reviewed 147 articles that demonstrated that small lower pole stones of <1 cm may be treated successfully with ESWL in children who are able to cooperate or under sedation; staghorn stones, are better treated by PCNL. Flexible ureterorenoscopy is considered a second option for smaller stones and an alternative for middle size stones in case of failure of ESWL or contraindications for PCNL. Conclusion: ESWL alone, for a large stone, or in a lower pole in uninephric children is not the standard of care. PCNL offer an appropriate and therapeutic modality in specific situation i.e. larger stones, the lower pole stones with stone free rate approaching 80%. Nevertheless, flexible ureteroscopy with the newest high definition cameras has a promising potential in reaching a 100% stone-free rate in the near future.